Links between blood pressure and medication intake, well-being, stress, physical activity and symptoms reported via a mobile phone-based self-management support system: a cohort study in primary care. Issue 8 (23rd August 2018) - Taft, Charles; Hallberg, Inger; Bengtsson, Ulrika; Manhem, Karin; Kjellgren, Karin
Abstract : Objectives: To explore relationships between patients' self-monitoring of blood pressure (BP) and their concurrent self-reports of medication intake, well-being, stress, physical activity and symptoms. Design: This study is a secondary analysis of a prospective study exploring the 8-week effectiveness of a mobile phone-based self-management support system for patients with hypertension. Setting: Four primary healthcare centres situated in urban and suburban communities in Sweden. Participants: 50 patients undergoing treatment for hypertension. Primary and secondary outcome measures: Associations between systolic (SBP) and diastolic blood pressure (DBP) and 10 self-report lifestyle-related variables were analysed using linear mixed effects modelling. Results: Medication intake, better well-being, less stress and greater physical activity were associated variously with lower same-day SBP and DBP. The single strongest association was found between medication intake and SBP, where failure to take medications was associated with an estimated 7.44 mm Hg higher SBP. To a lesser degree, medication intake was also associated with DBP, where DBP was 4.70 mm Hg higher in cases where medications were not taken. Well-being and stress were consistently associated with SBP and DBP, whereas physical activity was associated with only SBP. None of the symptoms—dizziness, headache, restlessness, fatigue or palpitations—were significantly associated with BP. Conclusions: Our findings that BP was associated with patients' BP management behaviours and experiences of well-being and stress, but not symptoms suggest that enabling persons with hypertension to monitor and track their BP in relation to medication intake, physical activity, well-being, stress and symptoms may be a fruitful way to help them gain first-hand understanding of the importance of adherence and persistence to treatment recommendations. Trial registration number: NCT01510301 ; Pre-results.